PENGARUH KUALITAS DAN HARGA TERHADAP VOLUME PENJUALAN BERAS PREMIUM PERUM BULOG SUB DIVISI REGIONAL WILAYAH V KEDU - R. A. Mufidah; K. Budiraharjo; D. Sumarjo (Universitas Wahid Hasyim, 2018)
The purpose of this research are to determine the factors that affect the volume of premium rice sales of Perum Bulog Sub Division Regional Region V Kedu and to know the effect of rice quality and price on it. Method that been used in this research is case study. Data collection used observation and interview method. Data source uses primary data and secondary data. Data analyze uses multiple linear regression analysis. The results of the research show that quality and price have simultaneous and partial effect on the sales volume of premium rice and both of them have same effect on sales volume of premium rice.Keywords: Premium rice, Bulog, quality and price, sales volume.